Madrasah teacher job satisfaction, how does it relate to work motivation? A meta-analysis - Juhji Juhji; Ilzamudin Ma’mur; Enung Nugraha; Naf’an Tarihoran; Encep Syarifudin (International Journal of Education, Teaching, and Social Sciences, 2022)
The low quality of education refers to teachers' low work motivation and job satisfaction. These two variables are important because they affect their performance in madrasas. Therefore, this paper aims to analyze the relationship between teacher work motivation and madrasah teachers job satisfaction in the last ten years. This research uses meta-analysis and systematic review using JASP 0.14.1.0 software. The data found as many as 25 papers through a search, and nine papers were selected according to predetermined characteristics. The data taken from the selected articles is the number of samples (N) and the correlation value (r) in each paper, and then the effect size is analyzed. The study results found that the effect size value resulting from the relationship between the two variables was 0.610, with a moderate category at a 95 per cent confidence level at an interval of 0.450 to 0.770. The meta-analysis results in this study have stated the consistency of the results of previous studies and have strengthened existing theories, so it can be concluded that there is a significant relationship between work motivation and madrasah teachers job satisfaction. Recommendations from the results of this study, it is necessary to conduct further research on job satisfaction of honorary teachers at every level of madrasah education.